The Land Acquisition Policy Analysis for Development in the Public Interest on The Construction of the Semarang-Demak Toll Road - Kusriyah, Sri; Rinda Listyawati, Peni; Ma'ruf, Umar (Sultan Agung Notary Law Review, 2025)
National development is a series of continuous development efforts that cover all aspects of community life, nation and state, to carry out the task of realizing national goals. The implementation of development must be adjusted to spatial planning as an effort made in the context of meeting current needs without reducing the ability of future generations to meet their needs. Land is a national wealth needed by humans both individually, business entities and governments in order to realize national development. This paper is to find out how the land acquisition planning policy is for development in the public interest related to the construction of the Semarang-Demak toll road in Demak Regency, to find out how the procedure for implementing land acquisition in Demak Regency. The writing method uses a normative legal approach method, secondary data as the main data, primary data as supporting data, then analyzed with public policy theory and justice theory. The results of the study show that the Semarang-Demak toll road development policy is in accordance with the Demak Regency Spatial Planning policy in Regional Regulation No. Perda No. 1 of 2020. Concerning Amendments to Regional Regulation No. 6 of 2011 concerning the Demak Regency Spatial Planning Plan for 2011-2031. This conformity is very important because the local government understands the most about land use. The compensation procedure for land acquisition for the Semarang-Demak toll road applies the principles of justice, humanity and protection of human rights through deliberation, so that people who relinquish their land control rights sincerely relinquish their land rights. as regulated by Law No. 2 of 2012 concerning Land Acquisition for Development in the Public Interest.